2002
DOI: 10.1055/s-2002-23146
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodic and Antimicrobial Diterpenic Acids from Viguiera hypargyrea Roots

Abstract: Two spasmolytic diterpene acids, ent-beyer-15-en-19-oic acid and ent-kaur-16-en-19-oic acid, have been isolated from the roots of Viguiera hypargyrea by bioassay-guided fractionation. Beyerenoic acid was also active against Staphylococcus aureus, Enterococcus feacalis and Candida albicans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…More recently, it was demonstrated that the inhibitory effect displayed by ent-beyer-15-en-19-oic acid, on electrically induced contractions of guinea-pig ileum, is more pronounced than that found for kaurenoic acid (Zamilpa et al, 2002). The structure of this compound is slightly different from that of kaurenoic acid because of some differences in ring D, such as the relative stereochemistry, the presence of a double bond between C-15 and C-16, a methyl group attached to C-13 and the lack of the exocyclic methylene group at C-16.…”
Section: Structure-activity Relationship Of Kauranes and Pimaranesmentioning
confidence: 96%
“…More recently, it was demonstrated that the inhibitory effect displayed by ent-beyer-15-en-19-oic acid, on electrically induced contractions of guinea-pig ileum, is more pronounced than that found for kaurenoic acid (Zamilpa et al, 2002). The structure of this compound is slightly different from that of kaurenoic acid because of some differences in ring D, such as the relative stereochemistry, the presence of a double bond between C-15 and C-16, a methyl group attached to C-13 and the lack of the exocyclic methylene group at C-16.…”
Section: Structure-activity Relationship Of Kauranes and Pimaranesmentioning
confidence: 96%
“…Furthermore, after incubation for 15 min, the inhibitory effect displayed by PA at both concentrations was much greater than that found for KA. Such findings indicate that structural differences between these compounds potentiate and accelerate the inhibitory activity displayed by PA. Zamilpa et al (2000) demonstrated that the inhibitory effect displayed by ent-beyer-15-en-19-oic acid on electrically induced contractions of guinea-pig ileum was more pronounced than that found for KA. The structure of this compound is slightly different from that of KA because of some differences in ring D. The other three rings (A, B and C) of both structures are identical.…”
Section: Discussionmentioning
confidence: 85%
“…It has been demonstrated that the inhibitory effect displayed by the kaurane ent-beyer-15-en-19-oic acid on electrically induced contractions of guinea-pig ileum was more pronounced than that found for KA (Zamilpa et al 2000). The structure of this compound is slightly different from that of KA because of some differences in ring D, such as the relative stereochemistry, the presence of a double bond between C-15 and C-16, a methyl group attached to C-13 and the lack of the exocyclic methylene group at C-16.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…During past decades, plants have well proved their potential to produce a wide spectrum of natural products with interesting bioactivities [1][2][3][4][5][6] . Among these, cyclic peptides and related congeners with unique structures and wide pharmacological profile [7][8][9][10] have received special attention which may prove better candidates to overcome the problem of wide spread increase of resistance towards conventional drugs.…”
Section: Introductionmentioning
confidence: 99%